Climate change in prehistory : the end of the reign of chaos - Burroughs, William James (Cambridge University Press, 2005)
This book explores the challenges that faced humankind in a glacial climate and the opportunities that arose when the climate improved dramatically after the Ice Age. It weaves together studies of the climate with anthropological, archaeological and historical studies, and will fascinate all those interested in climate and human development.